VALUATION ENVIRONMENTAL AND SOCIAL IMPACT DUE TO BANTARGEBANG INTEGRATED WASTE MANAGEMENT SITE (TPST) BASED ON PERCEPTION COMMUNITY OF TAMANRAHAYU VILLAGE, SETU DISTRICT, BEKASI REGENCY - Dwi Adianty, Denisa
IWM Site development often experiences resistance due to potential negative impacts on the surrounding community. Negative impacts that are not addressed can compromise community welfare. For this reason, risk management efforts are needed by considering the value of benefits and costs through economic valuation of the impacts arising from TPST. Implementation of risk management based on impact assessment results is used to develop strategies so that mitigation is sustainable in the long term. This research takes a case study of the impact of the Bantargebang TPST based on the perceptions of the Tamanrahayu Village community. Apply mixed method research through qualitative and quantitative descriptive analysis in identifying and quantifying the impact of TPST. Using a deductive approach to formulate cost and benefit variables from the economic valuation concept which will be tested through data collection and analysis, then conclusions will be drawn on the value of each variable as a result of NET. Bantargebang IWM Site has the impact of decreasing quality (water, air, soil, environmental aesthetics), health problems, social conflicts, traffic disruptions, changes in land/property prices and benefits from employment. The NET and NPV of the TPST is IDR -397,452,915,784.58. These results show that the cost value is greater than the benefit value. It was concluded that for the people of Tamanrahayu Village the existence of the Bantargebang TPST had more negative impacts than positive impacts. The largest proportion of negative impacts was a decrease in land/property prices (66.7%). Impact risk management is creating green belt 0 – 100 m, to reduce odor and noise, reduce the potential for respiratory diseases, and improve aesthetics. The NPV result is IDR 15,920,281,403.57, meaning development green belt provide benefits greater than the costs incurred. Another risk management is providing clean water infrastructure for 98.78% of the community. The NPV obtained is IDR 136,519,467,687.25, the results are positive, meaning that the development of clean water infrastructure has more positive impacts in the form of benefits of easy access to clean water and the potential to prevent people from skin and digestive diseases.